1995
DOI: 10.1161/01.cir.91.3.698
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Five Antihypertensive Monotherapies and Placebo for Change in Left Ventricular Mass in Patients Receiving Nutritional-Hygienic Therapy in the Treatment of Mild Hypertension Study (TOMHS)

Abstract: NH intervention with emphasis on weight loss and reduction of dietary sodium is as effective as NH intervention plus pharmacological treatment in reducing echocardiographically determined LVM, despite a smaller decrease in blood pressure in the NH intervention only group. A possible exception is that the addition of diuretic (chlorthalidone) may have a modest additional effect on reducing LVM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
125
0
11

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(145 citation statements)
references
References 47 publications
9
125
0
11
Order By: Relevance
“…10. After 12 months, in which all TOMHS participants received nutritional-hygienic treatment, there was no additional significant difference with regard to LV hypertrophy regression between the group that received low doses of active antihypertensive medications as opposed to placebo, with no significant interaction of treatment with sex.…”
Section: Female Sex and Clinical Variablesmentioning
confidence: 83%
See 2 more Smart Citations
“…10. After 12 months, in which all TOMHS participants received nutritional-hygienic treatment, there was no additional significant difference with regard to LV hypertrophy regression between the group that received low doses of active antihypertensive medications as opposed to placebo, with no significant interaction of treatment with sex.…”
Section: Female Sex and Clinical Variablesmentioning
confidence: 83%
“…After 12 months, in which all TOMHS participants received nutritional-hygienic treatment, there was no additional significant difference with regard to LV hypertrophy regression between the group that received low doses of active antihypertensive medications as opposed to placebo, with no significant interaction of treatment with sex. 10 Among LIFE patients, there was no systematic change in body weight in either sex between baseline and 12 months of follow-up. Similarly, Schmieder et al 29 showed in a meta-analysis of high-quality clinical trials that both systolic and diastolic blood pressure reductions were independent correlates of LV mass regression.…”
Section: Female Sex and Clinical Variablesmentioning
confidence: 87%
See 1 more Smart Citation
“…Several studies have showed that cardiac hypertrophy is reversed disproportionately by various antihypertensive drugs [4].…”
Section: Nephropathy 4 Retinopathymentioning
confidence: 99%
“…In ALLHAT, the baseline rate of echocardiographic LVH were similar in all three treatment groups (B4.5%), but no follow-up echocardiographic data on LVM reported. In the Treatment of Mild Hypertension Study (TOMHS), 15 chlorthalidone led to a greater reduction in LVM than doxazosin, amlodipine, enalapril, and acebutolol in 844 stage 1 hypertensive participants (20% were black) at each follow-up visit for 4 years, despite equivalent BP reduction. Interestingly, in the participants with chlorthalidone added as a second agent, the demonstration of an additional decrease in LVM further suggests an independent effect of chlorthalidone on reduction of LVM.…”
mentioning
confidence: 99%